أثر أبعاد الرضا الوظيفي لدى معلمي مدارس التعليم الأساسي بسلطنة عمان على تماثلهم التنظيمي = The impact of job satisfaction dimensions on organizational identification among schools’ teachers (5-10) in sultanate of Oman - Alshuhumi, Said R. A.; Al-Hidabi, Dawood Abdulmalek Yahya; Abdulwahab Al-Daba, Abdulmajid Mohamed (المؤسسة العربية للتربية والعلوم والآداب, 2022)
The aim of this research was to examine the effect of the dimensions of job satisfaction on the organizational identification among school teachers in Sultanate of Oman. The descriptive survey design was adopted in this quantitative study using cross-sectional method to collect data. A five likert-scale questionnaire consisting of (65) items was distributed amongst 1000 teachers in seven educational governorates in Oman. Stratified random sampling was employed to obtain (846) questionnaires, out these 846 participants 419 were males and 427 were males. SPSS version 26 was used to conduct the descriptive analysis, while AMOS (version 26) was used to perform confirmatory factor analysis (CFA) to assess the validity and reliability of this study model. AMOS was also used to examine the relationships between job satisfaction and organizational commitment. The results revealed a significant direct impact for three dimensions of job satisfaction (work conditions, salary and school administration) on teachers’ organizational identification. However, there is no direct effect for the other three dimensions of job satisfaction, i.e., professional development, educational supervision and social status. The study concluded with recommendations and suggestions for future studies.